Effects of strength training on blood lipoprotein concentrations in postmenopausal women - Cleiton Silva Correa; Bruno Costa Teixeira; Aline Bittencourt; Álvaro Reischak-Oliveira (Jornal Vascular Brasileiro, 2014)
Strength training is often identified as a contributing factor in prevention of diseases and as a non-pharmacological treatment for metabolic disorders and for control of body mass. Its protective effects and utility for management of disease are amplified in people at risk of diabetes mellitus and dyslipidemias, and cardiovascular diseases (CVD). Recently the benefits of strength training have been used to reduce the risk of these diseases emerging in postmenopausal women, who are at greater risk of CVD than men of the same age. Notwithstanding, little is known about the effects of strength training on metabolism of blood lipoproteins. The objective of this review was to compare the results of articles that have investigated the effects on lipoprotein concentrations of strength training in postmenopausal women. Current articles dealing with the subject, with publication dates from 1979 to 2012 and large numbers of citations by well-known researchers were identified on the Pubmed, Scopus and EBSCO databases. It was concluded that strength training possibly has an action that affects lipoprotein metabolism and concentrations in postmenopausal women.